(untitled) (Canadian Medical Education Journal, 2026)
Background: Leadership in Canadian medical education continues to be shaped by hierarchical, Western-derived paradigms that inadequately address systemic inequities, reconciliation, and the Calls to Action of the Truth and Reconciliation Commission. There is a pressing need for leadership models that reflect Indigenous worldviews and respond to the challenges of medical education in the twenty-first century. Purpose: This paper introduces the Pedagogy of Peace—a theoretical framework grounded in Haudenosaunee and Anishinaabe teachings—as a novel conceptual model for medical education leadership. While originally developed as a curricular framework, its teachings hold important implications for re-imagining how leadership is understood, practiced, and cultivated in academic medicine. Framework: The Pedagogy of Peace is structured around four interrelated dimensions: knowing (self-in-relation), understanding (nurturing a good mind), doing (strengths-based action), and honouring (peace-focused solutions). Together, these principles articulate a holistic and relational approach to leadership that emphasizes positionality, reciprocity, integrity, and balance across physical, mental, emotional, and spiritual domains. Implications: By positioning the Pedagogy of Peace alongside existing leadership competencies (e.g., CanMEDS, AFMC frameworks), this paper advances a vision of leadership that is relational, peace-focused, and strengths-based. This theoretical contribution suggests pathways for medical schools to engage meaningfully with reconciliation, diversify leadership practices, and embed Indigenous epistemologies into institutional governance. Conclusion: The Pedagogy of Peace offers a theoretically grounded, Indigenous-informed model for leadership in medical education. By shifting how leadership is conceptualized, it opens new possibilities for cultivating leaders who can guide Canadian medical education toward equity, sustainability, and reconciliation.